Eco-enzyme from Orange Peel as a Key Ingredient in Anti Acne Peel-off Gel Mask - Zummah, Atiqoh; Bahri, Saiful; Violando, Wiga Alif; Tyastirin, Esti (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2024)
This study aims to develop a peel-off gel mask formulated from orange peel eco-enzyme solution and its physical characteristics and antibacterial activity against Staphylococcus epidermidis. The resulting gel mask has organoleptic characteristics of transparent brownish color, thick gel consistency, and fresh sour-sweet aroma. Physical characteristic tests showed that the gel mask meets pharmaceutical requirements, namely: pH value 4.5-6.5, spreadability 5-7 cm, and drying time 15-30 minutes. The mask showed good homogeneity without aggregates, although it was a little difficult to peel off, but it was not easily torn, and had stable thermodynamic stability. Antibacterial tests revealed that the peel-off gel mask made from orange peel eco-enzyme was effective in inhibiting the growth of Staphylococcus epidermidis. The diameters of the inhibition zones of the P1, P2, and P3 masks were 2.5 ± 0.5 mm, 2.1 ± 0.35 mm, and 1.5 ± 0.5 mm, respectively. These results indicate the potential of eco-enzymes from orange peel as active ingredients for peel-off gel mask formulation for skin care, especially in inhibiting acne-causing bacteria.